Dose-Dependent Effects of Foliar Nano NPK and Zinc on Yield, Antioxidant Capacity, and Metabolic Profile of Sweet Pepper (Capsicum annuum L.) - S. T. Stojanova, Marina; Stojanova, Monika; Demiri, Sani; A. Djukic, Dragutin; Kaya, Yalcin (MDPI AG, 2026)
Foliar nanofertilization is increasingly being explored as a strategy to enhance crop nutritional quality; however, dose-dependent physiological and metabolic responses remain insufficiently defined. This study evaluated the effects of conventional NPK (20:20:20) and nano-formulated NPK combined with zinc (3 and 5 g/L) on the mineral composition, bioactive compounds, antioxidant capacity, and metabolic profile of sweet pepper (Capsicum annuum L., cv. ‘Dora’) grown under controlled conditions. Physicochemical characterization of the nanofertilizer by dynamic light scattering and transmission electron microscopy confirmed nanoscale primary particle size and revealed concentration-dependent aggregation behavior at higher Zn levels. Significant differences (p < 0.05) were observed among treatments in macro- and microelement content, total phenolics, flavonoids, carotenoids, ascorbic acid, and antioxidant activity. The application of nano NPK combined with 3 g/L Zn resulted in the highest accumulation of total phenolics, flavonoids, and vitamin C, accompanied by enhanced antioxidant capacity, suggesting stimulation of secondary metabolism. In contrast, the higher Zn concentration (5 g/L) further increased carotenoid content but was associated with elevated proline levels, indicating the onset of physiological stress. Multivariate analyses (PCA and ROC) supported dose-dependent metabolic modulation and confirmed that combinations of selected metabolites contributed to clearer differentiation between fertilization regimes. Overall, the results highlight the existence of an optimal nano-zinc application range that enhances fruit functional quality while avoiding stress-related metabolic imbalance, emphasizing the importance of physicochemical stability in nano-enabled fertilization strategies. While this study focused on a single sweet pepper cultivar, future research should explore other pepper species to evaluate whether similar dose-dependent nano Zn effects are observed.